Efficacy of a curcumin extract (Curcugen™) on gastrointestinal symptoms and intestinal microbiota in adults with self-reported digestive complaints: a randomised, double-blind, placebo-controlled study - Adrian L. Lopresti; Stephen J. Smith; Alethea Rea; Shavon Michel (BMC, 2021)
Abstract Background There is preliminary evidence to suggest curcumin can alleviate digestive symptoms in adults with self-reported digestive complaints and irritable bowel syndrome. However, in all these trials, curcumin was used as a component of a multi-herbal combination and there were consistent concerns associated with risk of bias in most studies. The goal of this study was to investigate the effects of a curcumin extract (Curcugen™) on gastrointestinal symptoms, mood, and overall quality of life in adults presenting with self-reported digestive complaints. Moreover, to determine the potential therapeutic mechanisms of action associated with curcumin, its effects on intestinal microbiota and small intestinal bowel overgrowth (SIBO) were examined. Methods In this 8-week, parallel-group, double-blind, randomised controlled trial, 79 adults with self-reported digestive complaints were recruited and randomised to receive either a placebo or 500 mg of the curcumin extract, Curcugen™. Outcome measures included the Gastrointestinal Symptom Rating Scale (GSRS), intestinal microbial profile (16S rRNA), Depression, Anxiety, and Stress Scale - 21 (DASS-21), Short Form-36 (SF-36), and SIBO breath test. Results Based on self-report data collected from 77 participants, curcumin was associated with a significantly greater reduction in the GSRS total score compared to the placebo. There was also a greater reduction in the DASS-21 anxiety score. No other significant between-group changes in self-report data were identified. An examination of changes in the intestinal microbial profile and SIBO test revealed curcumin had no significant effect on these parameters. Curcumin was well-tolerated with no significant adverse events. Conclusions The curcumin extract, Curcugen™, administered for 8 weeks at a dose of 500 mg once daily was associated with greater improvements in digestive complaints and anxiety levels in adults with self-reported digestive complaints. Compared to the placebo, there were no significant changes in intestinal microbiota or SIBO; however, further research using larger samples and testing methods that allow more detailed microbial analyses will be important. An investigation into other potential mechanisms associated with curcumin's gastrointestinal-relieving effects will also be important such as examining its influence on the intestinal barrier function, inflammation, neurotransmitter activity, and visceral sensitivity. Trial registration Australian New Zealand Clinical Trials Registry, Trial ID. ACTRN12619001236189 . Registered 6 September 2019.